Spaces, displacements, writing and strategies of identity construction in Afuera crece un mundo by Adelaida Fernandez Ochoa - (:unkn) unknown (My University, 2021)
This article analyses the strategies of construction and affirmation of identity, and more specifically, of African identity in Afuera crece un mundo (2017) by Adelaida Fernandez Ochoa. This text is, above all, the story of a displacement, of a journey: that of Nay, a freed slave, and her son Sundiata, towards Africa, towards their origins, towards freedom. The story also raises the question of the articulation between gender and identity, Nay (as a black woman in a colonial society ruled by the white man) being doubly excluded, doubly silenced. This contribution analyses in particular the question of nomination and innomination, genealogy and origins, speech and writing as instruments of identity affirmation. Particular attention will be paid to the links that are established, in the course of the novel, between identity, space and displacement: the narrative, in which Nay's and Sundiata's voices alternate, in fact establishes a dialectic between three spaces: the space where one is, the space where one comes from (the space of origins, of roots) and the space where one is going, and posits the return to the space of origins, Africa, as the only true condition of being and of freedom. But other ways of constructing identity, other strategies for putting down roots, are evoked in the background, notably through the character of Brígida.
Keywords: African Research